Exploring the experience of an enhanced recovery programme for gynaecological cancer patients: a qualitative study - Archer, Stephanie (Perioper Med (Lond), 2014)
BACKGROUND: Perioperative enhanced recovery programmes (ERPs), identified as initiatives that improve care and save money, have been adopted by NHS Improvement and are currently being rolled out across many surgical departments within the NHS. To date, five papers have specifically explored patients’ experiences of ERPs; none, however, has explored the gynaecological cancer patient experience. METHODS: In total, 14 women (mean age, 66 years) participated in an audio-recorded face-to-face or telephone interview in which they discussed their experience of taking part in an ERP. The resulting data were transcribed verbatim and analysed using interpretative phenomenological analysis. RESULTS: Two main themes emerged from the analysis. The first, ‘Taking part in the programme’, highlights two important aspects of the ERP: being given an opportunity to receive information and, following this, to build knowledge about the programme. The theme also explores the challenges associated with the programme, particularly around getting mobile and complying with its demands - the women report experiencing a constant battle between intuition and instruction. The second theme, ‘Home’, focuses on the role home plays in motivating the patients to aim for an early discharge from hospital. Patients describe their need to return to a suitable home and the need for support from others. They also discuss the importance of the follow-up phone call. CONCLUSION: Overall, the patients in this study positively assessed the individual aspects of the ERP, in particular, information resources, the availability of the physiotherapist and the delivery of follow-up phone calls. These findings highlight the importance of developing and maintaining individual aspects of ERPs over time, to ensure their sensitivity and responsiveness to patient needs.